El formismo: un paradigma para repensar las religiosidades profanas - Carretero Pasín, Ángel Enrique (Nómadas. Critical Journal of Social and Juridical Sciences, 2005)
In this work the formismo is approached as a perspective of sociological analysis of the profane religiousness. First, it tries to clarify the meaning attributed by Georg Simmel to the notion of form and his implications for the study of a type of religiousness that passes for riverbeds foreign to the institutional religiousness. Then, it gets in the notion so that Michel Maffesoli uses like tool theoretically destined to interpret a multitude of expressions that nest in the contemporary culture. In both cases, there is emphasized how the form is the instance that, come from the relations that are interwoven between certain individuals, makes possible the crystallization of a community link.